SOSIALISASI MOTIVASI SISWA SISWI SMK RAUDHATUL MU’AWANAH DALAM PROGRAM KREATIFITAS MANAJEMEN KEWIRAUSAHAAN DI ERA DIGITAL - Sapari, Sapari; Putra, Feby Arma; Mulyani, Yeni; Alfiah, Siti; Nilawati, Neli (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
The Motivation Socialization Activity for Students of SMK Raudhatul Mu'awanah in the Entrepreneurial Management Creativity Program in the Digital Era was carried out as an effort to foster entrepreneurial spirit and ability among vocational school students. In today's digital era, many students still have low motivation to be entrepreneurs and tend to be oriented towards being job seekers rather than job creators. In addition, the limited understanding of modern entrepreneurial management concepts and the lack of access to training and assistance in the development of technology-based business ideas are the main problems faced by students. This community service program aims to help students of SMK Raudhatul Mu'awanah in providing motivation and practical understanding of the importance of creativity and innovation in the world of entrepreneurship. Through this socialization activity, students are introduced to modern entrepreneurial management concepts that are relevant to the development of the digital world, such as the use of social media, e-commerce, and digital marketing strategies in building a business. This activity also emphasizes the importance of critical thinking, collaboration, and networking between students, teachers, and local business actors, so as to create an environment that supports the spirit of entrepreneurship. The implementation method is carried out through socialization activities with a participatory approach, in the form of material delivery, interactive discussions, and simple simulations on how to maintain and increase motivation about entrepreneurship creatively through digital. The material covers the basic concepts of motivation, the factors that affect motivation, as well as practical steps such as time management, goal setting, and strengthening the growth mindset. With this method, students not only gain knowledge, but also hands-on experience in understanding the importance of Entrepreneurial Creativity in the Digital Era for their future. The expected results of this activity are increased motivation and interest in students to be creative entrepreneurs through digital roles, the emergence of new technology-based business ideas, and the formation of student entrepreneurship groups (studentpreneur clubs) as a forum for the development of entrepreneurship programs at SMK Raudhatul Mu'awanah. Keywords: Creativity, Entrepreneurship in the Digital Era, SMK Raudhatul Mu'awanah.